The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3357/amhp.4663.2016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in Military Aircrew Using a Candidate Definition

Abstract: Reported prevalence of MetS highlights an urgent need to define preventive strategies to minimize loss of trained manpower among military aircrew. Flight surgeons have an important role to play to educate aircrew about modifying their lifestyle to reduce morbidity and mortality among themselves in the future. Sharma S, Chandrashekar AM, Singh V. Metabolic syndrome in military aircrew using a candidate definition. Aerosp Med Hum Perform. 2016; 87(9):790-794.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Six studies had reported trends in the prevalence of CMRFs over a time period [22,24,26,28,30,40], so that their weighted prevalence was considered as an overall prevalence. Among all publications, 15 studies were conducted in the American countries [9, 19, 20, 24-27, 29-32, 36, 38, 41, 51], 13 in Europe [22, 28, 33-35, 37, 39, 40, 44, 45, 48-50] and 9 in Asia [13,15,18,21,23,42,43,46,47]. Table 1 shows the general characteristics of the selected studies for the prevalence of MetS.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Six studies had reported trends in the prevalence of CMRFs over a time period [22,24,26,28,30,40], so that their weighted prevalence was considered as an overall prevalence. Among all publications, 15 studies were conducted in the American countries [9, 19, 20, 24-27, 29-32, 36, 38, 41, 51], 13 in Europe [22, 28, 33-35, 37, 39, 40, 44, 45, 48-50] and 9 in Asia [13,15,18,21,23,42,43,46,47]. Table 1 shows the general characteristics of the selected studies for the prevalence of MetS.…”
Section: Study Characteristicsmentioning
confidence: 99%